Accounting for multiple ecosystem services in a simulation of land-use decisions: Does it reduce tropical deforestation? - Knoke, Thomas; Paul, Carola; Rammig, Anja; Gosling, Elizabeth; Hildebrandt, Patrick; Härtl, Fabian; Peters, Thorsten; Richter, Michael; Diertl, Karl-Heinz; Castro, Luz Maria; Calvas, Baltazar; Ochoa, Santiago; et al. (Global Change Biology, 2020)
Conversion of tropical forests is among the primary causes of global environmental change. The loss of their important environmental services has prompted calls to integrate ecosystem services (ES) in addition to socio-economic objectives in decision-making. To test the effect of accounting for both ES and socio-economic objectives in land-use decisions, we develop a new dynamic approach to model deforestation scenarios for tropical mountain forests. We integrate multi-objective optimization of land allocation with an innovative approach to consider uncertainty spaces for each objective. These uncertainty spaces account for potential variability among decision-makers, who may have different expectations about the future. When optimizing only socio-economic objectives, the model continues the past trend in deforestation (1975–2015) in the projected land-use allocation (2015–2070). Based on indicators for biomass production, carbon storage, climate and water regulation, and soil quality, we show that considering multiple ES in addition to the socio-economic objectives has heterogeneous effects on land-use allocation. It saves some natural forest if the natural forest share is below 38%, and can stop deforestation once the natural forest share drops below 10%. For landscapes with high shares of forest (38%–80% in our study), accounting for multiple ES under high uncertainty of their indicators may, however, accelerate deforestation. For such multifunctional landscapes, two main effects prevail: (a) accelerated expansion of diversified non-natural areas to elevate the levels of the indicators and (b) increased landscape diversification to maintain multiple ES, reducing the proportion of natural forest. Only when accounting for vascular plant species richness as an explicit objective in the optimization, deforestation was consistently reduced. Aiming for multifunctional landscapes may therefore conflict with the aim of reducing deforestation, which we can quantify here for the first time. Our findings are relevant for identifying types of landscapes where this conflict may arise and to better align respective policies.
CRIS-Team Scopus Importer:2020-02-25
Keywords: biodiversity; ecosystem services; Ecuador; land allocation; landscape restoration; robust optimization

Afforestation or intense pasturing improve the ecological and economic value of abandoned tropical farmlands - Knoke, Thomas; Bendix, Joerg; Pohle, Perdita; Hamer, Ute; Hildebrandt, Patrick; Roos, Kristin; Gerique, Andrés; Sandoval, Maria L.; Breuer, Lutz; Tischer, Alexander; Silva, Brenner; Calvas, Baltazar; et al. (Nature Communications, 2014)
Increasing demands for livelihood resources in tropical rural areas have led to progressive clearing of biodiverse natural forests. Restoration of abandoned farmlands could counter this process. However, as aims and modes of restoration differ in their ecological and socio-economic value, the assessment of achievable ecosystem functions and benefits requires holistic investigation. Here we combine the results from multidisciplinary research for a unique assessment based on a normalization of 23 ecological, economic and social indicators for four restoration options in the tropical Andes of Ecuador. A comparison of the outcomes among afforestation with native alder or exotic pine, pasture restoration with either low-input or intense management and the abandoned status quo shows that both variants of afforestation and intense pasture use improve the ecological value, but low-input pasture does not. Economic indicators favour either afforestation or intense pasturing. Both Mestizo and indigenous Saraguro settlers are more inclined to opt for afforestation.
Keywords: Agroecology; Restoration ecology

An introduction to ethnoecology and ethnobotany, theory and methods - Gerique-Zipfel, Andres (2006)
UnivIS-Import:2015-04-20:Pub.2008.nat.dgeo.IG.LGIPDH.sustai

Biodiversity as a Resource: Plant Use and Land Use among the Shuar, Saraguros, and Mestizos in Tropical Rainforest Areas of Southern Ecuador - Gerique-Zipfel, Andres (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2011)

Biodiversity as a Resource: Plant Use, Land Use, and Nature Conservation in Shuar, Saraguro, and Mestizo Communities in South-Eastern Ecuador - Gerique-Zipfel, Andres (Medicinal Plants and the Legacy of Richard E. Schultes – Proceedings of the Botany 2011 Symposium Honoring Dr. Richard E. Schultes. Trujillo, 2012)

Climate change and tourism in South and Central America - Navarro-Drazich, Diego; Christel, Lucas G.; Gerique-Zipfel, Andres; Grimm, Isabel; Rendón, Maria Luisa; Schlemer Alcântara, Liliane; Abraham, Yasmin; Conde, Maria del Rosario; De Simón, Cecilia (Journal of Sustainable Tourism, 2023)
This paper assesses the state of knowledge of climate change and tourism in South and Central America, with a special focus on the characteristics of the tourism sector, the particularities of climate risks of the region and the sectoral GHG contribution. We conducted a scientific literature review (by region and by country) in Spanish, Portuguese and English using publications in the Scopus and Google databases to the end of 2021. In parallel, we performed a search for institutional publications, programs, and strategies on climate change and tourism in South and Central American countries. This analysis identified the main challenges and potentialities between tourism and climate change in the region. Among the main findings is the limited number of studies and lack of primary data to inform policy formulation and tourism planning. Likewise, national, and regional public policies specific to tourism are scarce, while multisectoral climate plans have only recently been developed and, consequently, are difficult to evaluate.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Central America; climate change; South America; Tourism

Confronting sustainable intensification with uncertainty and extreme values on smallholder tropical farms - Knoke, Thomas; Gosling, Elizabeth; Reith, Esther; Gerique, Andrés; Pohle, Perdita; Valle Carrion, Liz; Ochoa Moreno, Wilman Santiago; Castro, Luz Maria; Calvas, Baltazar; Hildebrandt, Patrick; Doellerer, Martin; Bastit, Felix; et al. (SUSTAIN SCI, 2022)
Sustainable intensification of agricultural lands might reconcile the conservation of tropical forest with food production, but in-depth assessments considering uncertainty and extreme values are missing. Uncertainty prohibits mapping probabilities to potential future states or ranking these states in terms of their likelihood. This in turn hampers the assessment of possible decision outcomes. Here, we use simulations to investigate how uncertainty may influence the social acceptability of alternative land-use strategies to halt tropical deforestation (including sustainable intensification), based on indicators representing farmer satisfaction. The results show how extreme values (worst values) for indicators of farmer satisfaction may undermine the adoption of sustainable intensification. We demonstrate that a pure forest conservation strategy leads to lower food production, but outperforms a sustainable intensification strategy that maintains food security. Pure forest conservation performed better, i.e., could secure higher farmer satisfaction, than sustainable intensification across a range of indicator groups. This suggests strong barriers to achieving sustainable intensification. Using agricultural subsidies breaks the dominance of pure forest conservation by enhancing the economic returns of sustainable intensification. We discuss the importance of access to labor and farmers’ preferences for the use of already cleared lands, which achieved the worst values under sustainable intensification and conclude that any assessment of land-use strategies requires careful consideration of uncertainty and extreme values.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Agricultural intensification; Farmer preferences; Land allocation; Multiple objective robust optimization; Off-farm income; Tropical deforestation

Current Cultural Services: Landscape History - Rodriguez, Fernando; Bräuning, Achim; Gerique-Zipfel, Andres; Behling, Hermann; Volland, Franziska (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)

Current Provisioning Ecosystem Services for the Local Population: Landscape Transformation, Food Production, and Plant Use - Pohle, Perdita; Gerique-Zipfel, Andres; López Sandoval, María; Spohner, Regine (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Eduador, 2013)

Current provisioning services: Conservation, Management of natural Forests and Reforestation of Pastures - Weber, Michael; Stimm, Bernd; López Sandoval, María; Gerique-Zipfel, Andres; Pohle, Perdita; Hildebrandt, Patrick; Knoke, Thomas; Palomeque, Ximena; Calvas, Baltazar; Guenter, Sven; Aguirre, Nikolay; Kübler, Daniel (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)

Current Provisioning Services: Pasture Development and Use, Weeds (Bracken) and Management - Roos, Kristin; Bendix, Jörg; Curatola Fernández, Giulia; Adams, Julia; Gerique-Zipfel, Andres; Hamer, Ute; Hildebrandt, Patrick; Knoke, Thomas; Meyer, Hanna; Pohle, Perdita; Potthast, Karin; Thies, Boris; et al. (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)

Effectiveness and distributional impacts of payments for reduced carbon emissions from deforestation - Knoke, Thomas; Weber, Michael; Barkmann, Jan; Pohle, Perdita; Calvas, Baltazar; Medina, Carolina; Aguirre, Nikolay; Guenter, Sven; Stimm, Bernd; Mosandl, Reinhard; von Walter, Frank; Maza, Byron; et al. (Erdkunde, 2009)
This paper analyses the effectiveness and distributional effects of payments to avoid tropical deforestation. As a first aspect, we investigated whether or not expected payments for avoided deforestation would be acceptable for tropical farmers in Southern Ecuador, with the study area located directly adjacent to the Podocarpus National Park. Second, we explored possible distributional effects resulting from voluntary or mandatory remuneration schemes to avoid deforestation. Finally, a productive sustainable land use was conceptualised to be combined with payments for avoided deforestation to avoid leakage (i.e. deforestation processes elsewhere when avoided at a given farm). Farm level land use scenarios with ("business as usual") and without deforestation ("conservation strategy") were compared. Compensation per Mg Carbon (C) that is not emitted into the atmosphere under the "conservation strategy" was derived to achieve a monetary land net present value (NPV, sum of discounted future net revenues) equal to the NPV obtained under "business as usual". Avoided carbon emissions were computed from above ground C in tropical forests of the project area and supplemented by information on soil carbon from another study. Economic data for cattle pasturing were obtained from a farm survey (130 households) to investigate distributional effects. To derive sustainable land use concepts, a risk sensitive bioeconomic farm model was used that considered effects of risk compensation when combining pasture with reforestation of abandoned farm lands and selective logging of natural forests. The results showed that only a few farmers (20 out of 130) would possibly accept a compensation price of US 10 per Mg avoided C emission, a C-compensation that is believed by other authors to reduce deforestation by 65%. Rather a compensation of around US 25 per Mg C was necessary to address compensation requirements of farmers who hold 50% of the tropical forest area in our study. The implementation of a voluntary remuneration scheme for avoided deforestation would not introduce systematic distributional effects (such as that only the biggest farmers would benefit from compensation), while a mandatory and enforced ban on deforestation coupled with a "fair" compensation payment equal to mean compensation requirements may lead to undesirable effects for many farmers. Finally, we demonstrate a mixed sustainable land use concept that depended on cheap credits for reforestation of abandoned pasture lands. This concept was able to stop farm level deforestation and to enlarge the economic value of farms through various combined land use options (agricultural and forestry options). The combination of land uses led to risk compensatory effects and a more efficient land use by reintegrating unproductive abandoned areas back into the economical process. In our conclusion a combination of payments for avoided deforestation along with productive land use concepts provided a viable solution for tropical forest conservation.
UnivIS-Import:2015-03-09:Pub.2009.nat.dgeo.IG.LGIPDH.effect
Keywords: Tropical forest conservation; conservation payments; carbon storage; sustainable land use

El Chaltén, Argentinian Patagonia: A successful combination of conservation and tourism? - Gerique-Zipfel, Andres; Vanselow, Kim André (Socio-Environmental Research in Latin America, 2023)
El Chaltén is a village created in 1985 within Los Glaciares National Park, in Argentine Patagonia. Since 1985, this urban center has experienced rapid development due to immigration and nature tourism. We use the concept of naturbanization to investigate why and how El Chaltén was created, who are its inhabitants and visitors, and above all, what are the socio-environmental dynamics and impacts of the resulting urbanization process within a national park. To answer these questions, we use a mixed methodology that includes fieldwork, quantitative and qualitative interviews, and remotely sensed data time series based on the Normalized Difference Vegetation Index. Although our research finds limited negative environmental impacts caused by the creation of a village inside a national park, further urbanization can endanger the fragile balance between a growing population and tourism demand on the one side and effective conservation on the othe
Keywords: Nature-based tourism; prtected areas; Argentina; Patagonia; El Chaltén; remote sensing; naturbanization

Exploring farmer perceptions of agroforestry via multi-objective optimisation: a test application in Eastern Panama - Gosling, Elizabeth; Reith, Esther; Knoke, Thomas; Gerique, Andrés; Paul, Carola (Agroforestry Systems, 2020)
Understanding farmers’ perceptions of and preferences towards agroforestry is essential to identify systems with the greatest likelihood of adoption to inform successful rural development projects. In this study we offer a novel approach for evaluating agroforestry systems from the farmer perspective. The approach couples rapid rural appraisal and normative optimisation techniques to determine favourable land-use compositions for meeting various socio-economic and ecological goals, based on farmers’ empirical knowledge and preferences. We test our approach among smallholder farmers in Eastern Panama, obtaining data from household interviews and using hierarchical cluster analysis to identify farm groups with similar land-use and income characteristics. We found that moderate differences in farmers’ perceptions between these groups altered the type and share of agroforestry included in the optimised land-use portfolios that balance the achievement of 10 pre-selected socio-economic and ecological objectives. Such differences provide valuable information about potential acceptability of agroforestry within each group. For example, we found that farmers who derive most of their farm income from crops may be more willing to adopt silvopasture, whereas farmers who are more economically dependent on cattle may benefit from diversifying their land-use with alley cropping. We discuss the potential of this modelling approach for participatory land-use planning, especially when dealing with small sample sizes and uncertainty in datasets.
CRIS-Team Scopus Importer:2020-07-10
Keywords: Alley cropping; Hierarchical cluster analysis; Land allocation; Participatory rural appraisal; Robust optimisation; Silvopasture

Farmers’ Preferences of Proposed Land Use Options - Pohle, Perdita; López Sandoval, María; Gerique-Zipfel, Andres (2012)

Geografía del arte callejero: La distribución espacial de un arte controvertido. El caso de Valparaíso. - Gemeinholzer, Jan; Gerique-Zipfel, Andres; Richter, Michael (Revista Geográfica de Valparaiso, 2021)
En este artículo se analiza el fenómeno del arte callejero desde una perspectiva geográfica, entendiendo por dicho arte tanto los complejos murales de gran calidad artística y persistencia como los grafitis de fugaz existencia y autoría poco clara. El estudio se basa en análisis bibliográfico y un trabajo de campo en la ciudad de Valparaíso. Los resultados indican que la ubicación geográfica de las diferentes expresiones del arte callejero varían a escala local y mundial. Por ejemplo, en las ciudades de rico colorido de América Latina el arte callejero de vistosos colores es particularmente frecuente. A nivel local, destaca Valparaíso. México desempeña el papel de pionero, ya que en el muralismo de los "Tres Grandes" (Orozco, Siqueiros, Rivera) se encuentra uno de los orígenes de los murales modernos. En la capital del arte y la cultura de Chile, Valparaíso, una actitud liberal tanto por parte de los residentes como de la administración de la ciudad hacia los artistas de arte callejero ha provocado un boom que contribuye a su atractivo turístico. Este artículo aclara hasta qué punto los murales constituyen el momento inicial para las decoraciones artísticas de vehículos, y el por qué los grafiteros prefieren los "lugares perdidos" para su obra.<br
Keywords: Street Art; Arte callejero; Valparaíso; muralismo; Muralismus; grafiti; Graffiti

Human Ecological Dimensions in Sustainable Utilization and Conservation of Tropical Mountain Forests under Global Change - Pohle, Perdita; Gerique-Zipfel, Andres; López Sandoval, María (Biodiversity Hotspot Tropical Mountain Rainforest, 2016)

Human ecological dimensions in sustainable utilization and conservation of tropical mountain rain forests under global change in southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres; Park, Martina; López Sandoval, María (Tropical Rainforests and Agroforests under Global Change: Ecological and Socio-economic Valuations, 2010)
UnivIS-Import:2015-04-20:Pub.2010.nat.dgeo.IG.LGIPDH.humane

Indigenous concepts of land use and biodiversity conservation in southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres (Publications of the presentations on the III. Congress on the Conservation of Biodiversity of the Andes and the Amazon Region, 2005)
UnivIS-Import:2015-04-16:Pub.2005.nat.dgeo.IG.LGIPDH.indige_6

Inventing the savage: the Sapara people of the Ecuadorian Amazon in 19th-century travel writing - Rosado Valencia, Erika; Jansen, Silke; Gerique-Zipfel, Andres (Journal de la Société des américanistes, 2024)
In this article, we examine the discursive construction of the Sapara people of the Ecuadorian Amazon in the writings of travelers who explored the region in the second half of the 19th century. We focus mainly on the ways in which these writings reflect prevailing ideologies of the time, according to which “civilized” human societies could be distinguished from “savage” ones. In doing this, we analyze the representation of different aspects of the Sapara culture, such as agriculture and working habits, gender relations and sexual practices and the art of war and leisure. We frame our analysis in the theoretical proposal of Irvine and Gal for the ideological construction of cultural difference through the semiotic processes known as rhematization, fractal recursivity, and erasur
Keywords: Ecuadorian Amazon; cultural difference; 19th-century travel writing; semiotic approach; Sapara people; savagery

Inventing the savage: the Sapara people of the Ecuadorian Amazon in 19th-century travel writing L’invention du sauvage : le peuple sapara de l’Amazonie équatorienne dans les récits de voyage du XIXe siècle La invención del salvaje: el pueblo sapara de la Amazonía ecuatoriana en los relatos de viajes del siglo XIX - Rosado Valencia, Erika; Jansen, Silke; Gerique-Zipfel, Andres (Journal de la Société des américanistes, 2024)
In this article, we examine the discursive construction of the Sapara people of the Ecuadorian Amazon in the writings of travelers who explored the region in the second half of the 19th century. We focus mainly on the ways in which these writings reflect prevailing ideologies of the time, according to which “civilized” human societies could be distinguished from “savage” ones. In doing this, we analyze the representation of different aspects of the Sapara culture, such as agriculture and working habits, gender relations and sexual practices and the art of war and leisure. We frame our analysis in the theoretical proposal of Irvine and Gal for the ideological construction of cultural difference through the semiotic processes known as rhematization, fractal recursivity, and erasure.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 19th-century travel writing; cultural difference; Ecuadorian Amazon; Sapara people; savagery; semiotic approach

Land cover change in the Andes of southern Ecuador-Patterns and drivers - Curatola Fernández, Giulia; Obermeier, Wolfgang; Gerique, Andrés; López Sandoval, María; Lehnert, Lukas; Thies, Boris; Bendix, Jörg (Remote Sensing, 2015)
In the megadiverse tropical mountain forest in the Andes of southern Ecuador, a global biodiversity hotspot, the use of fire to clear land for cattle ranching is leading to the invasion of an aggressive weed, the bracken fern, which is threatening diversity and the provisioning of ecosystem services. To find sustainable land use options adapted to the local situation, a profound knowledge of the long-term spatiotemporal patterns of land cover change and its drivers is necessary, but hitherto lacking. The complex topography and the high cloud frequency make the use of remote sensing in this area a challenge. To deal with these conditions, we pursued specific pre-processing steps before classifying five Landsat scenes from 1975 to 2001. Then, we quantified land cover changes and habitat fragmentation, and we investigated landscape changes in relation to key spatial elements (altitude, slope, and distance from roads). Good classification results were obtained with overall accuracies ranging from 94.5% to 98.5% and Kappa statistics between 0.75 and 0.98. Forest was strongly fragmented due to the rapid expansion of the arable frontier and the even more rapid invasion by bracken. Unexpectedly, more bracken-infested areas were converted to pastures than vice versa, a practice that could alleviate pressure on forests if promoted. Road proximity was the most important spatial element determining forest loss, while for bracken the altitudinal range conditioned the degree of invasion in deforested areas. The annual deforestation rate changed notably between periods: 1.5% from 1975 to 1987, 0.8% from 1987 to 2000, and finally a very high rate of 7.5% between 2000 and 2001. We explained these inconstant rates through some specific interrelated local and national political and socioeconomic drivers, namely land use policies, credit and tenure incentives, demography, and in particular, a severe national economic and bank crisis.
Keywords: Andes; Attractors of landscape change; Bracken fern; Deforestation drivers; Ecuador; Fragmentation; Image pre-processing; Land cover change; Landsat; Remote sensing

Landscape change in Southern Ecuador: An indicator-based and multi-temporal evaluation of land use and land cover in a mixed-use protected area - López, Santiago; López-Sandoval, María Fernanda; Gerique, Andrés; Salazar, Joel (Ecological Indicators, 2020)
In this study, we evaluate landscape composition and configuration changes between 1989 and 2016 associated with the establishment and downsizing of the Corazón de Oro Protective Forest, a mixed-use protected area in the tropical Andes of Southern Ecuador. We identify the most significant land use/land cover changes and the implications for management and conservation linked to these two events. We rely on remote sensing, landscape indicators, statistical analysis, and expert knowledge to evaluate landscape structure. This combination of methods allowed us to quantify diversity, evenness, proportional abundance, dominance, surface area, and isolation trajectories to assess compositional and configurational differences marked by the protected area's creation and downsizing. While we found that landscape composition remained relatively unchanged over time, the creation of the protected area significantly altered landscape configuration but curbed human pressure on evergreen montane habitats. The downsizing event increased anthropogenic pressure on highland páramo vegetation. Our findings demonstrate that some aspects of landscape configuration vary independently of composition. Most importantly, however, we show that protected area formation and downsizing can significantly alter the spatial arrangement and size of transitional areas, which, in turn, may affect landscape dynamics with implications for energy flow and habitat function. The suite of landscape metrics used in this study are effective indicators that can assist managers monitor the performance of mixed-use protected areas.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Composition and configuration; Downsizing; Landscape indicators; Remote sensing; Southern Ecuador

Landscape History, Vegetation History, and Past Human Impacts - Rodriguez, Fernando; Bräuning, Achim; Gerique-Zipfel, Andres; Behling, Hermann; Volland, Franziska (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)
Three pollen profiles reveal vegetation changes during the past 16,500 years of the Podocarpus National Park (PNP) in the Southern Ecuadorian Andes. Andean glaciers retreated after the Last Glacial Maximum and the Younger Dryas cold interval, accompanied by a marked decline of páramo vegetation between 11660 and 4280 b.p., and the expansion of subpáramo vegetation. Polylepis was widespread during the warm early Holocene, whereupon páramo vegetation increased after 4200 b.p. The upper montane forest became abundant after 4200 b.p., and an increase of páramo taxa since 500 b.p. indicates moister climate since then. Charcoal particle concentration maxima are evident between 1800 to 1600 b.p. and 600 to 400 b.p. The mountain region became permanently settled at the end of the nineteenth century when the exploitation of natural resources was initiated. Decadal variations in ring-width chronology from Cedrela montana are possibly related to large-scale atmospheric pressure variations in the tropical Pacific Ocean.

Las plantas medicinales y su uso en el sur del Ecuador - Gerique-Zipfel, Andres (Miradas desde la geografía,arquitectura, territorio hacia la salud pública, 2009)

Mycorrhiza networks promote biodiversity and stabilize the tropical mountain rain forest ecosystem – perspectives for understanding complex communities - Kottke, Ingrid; Setaro, Sabrina; Haug, Ingeborg; Herrera, Paulo; Cruz, Darío Javier; Fries, Andreas; Adams, Julia; Homeier, Jürgen; Werner, Florian; Gerique-Zipfel, Andres; Suárez, Juan Pablo (Ecosystem Services, Biodiversity and Environmental Change in a Tropical Mountain Ecosystem of South Ecuador, 2013)

Naturbanisierung: Ein Ansatz zur Untersuchung der Wechselbeziehungen zwischen Nationalparks und Tourismus im ländlichen Raum - Gerique-Zipfel, Andres; Knode, Nina (Naturtourismus – Chancen und Herausforderungen, 2016)

Plant use, land use, and conservation - Gerique-Zipfel, Andres (2012)

Rechtliche und politische Rahmenbedingungen als Grundlage für sozial-ökologische Transformationen. Die Themenfelder Nachhaltigkeit, ländliche Räume, Klima- und Gewässerschutz, Biodiversität, Wald, Landwirtschaft und Energie - Pohle, Perdita; Brönner, Maximilian; Gerique-Zipfel, Andres; Kieslinger, Julia; Lederer, Lauritz (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2021)

Sitting on a ticking bomb? A political ecological analysis of conservation conflicts in the Alto Nangaritza Valley, Ecuador - Gerique-Zipfel, Andres; López Sandoval, María; Pohle, Perdita (Erde, 2017)
The Alto Nangaritza Valley in southeastern Ecuador constitutes one of the most important hotspots of biodiversity worldwide. Concerns about the exploitation of natural resources in this area have led to the creation of different types of conservation areas and policies during the last 30 years. These territorially-based conservation measures have provoked a series of conflicts between them conservation advocates and the Ecuadorian authorities on one side, and the local population who relies on the exploitation of natural resources on the other side. We analyze these conservation conflicts from a political ecological point of view, beginning with an introduction to the historical context, and then we consider the role of changing national development and spatial transformation priorities in these conflicts. Finally, in the face of the neoextractivist path that Ecuador has taken, we advocate even power relations between resource extraction and conservation policie
Keywords: Conservation; conflicts; Ecuador; Political Ecology; neoextractivism

Sustainable and Non Sustainable Use of Natural Resources by Indigenous and Local Communities - Pohle, Perdita; Gerique-Zipfel, Andres (Gradients in a Tropical Mountain Ecosystem of Ecuador, 2008)

Sustainable Livelihood in Southern Mustang District - Haffner, Willibald; Benachib, Hafida; Brock, Christoph; Gerique-Zipfel, Andres; Merl, Kerstin; Morkel, Silke; Park, Martina; Pohle, Perdita; Titz, Alexandra; Werning, Knut (Translating Development. The case of Nepal., 2003)
UnivIS-Import:2015-04-20:Pub.2003.nat.dgeo.IG.zentr.sustai

The Shuar’s Traditional Resource-Use System under Threat: Colonization Pressure in the Alto Nangaritza - Pohle, Perdita; Gerique-Zipfel, Andres; López Sandoval, María; Buitrón Cañadas, Viviana (2012)

Traditional ecological knowlegde and biodiversity management in the Andes of southern Ecuador - Pohle, Perdita; Gerique-Zipfel, Andres (Geographica Helvetica, 2006)
The tropical mountain rainforests of the eastern Andean slopes in southern Ecuador have an extraordinary rich biodiversity. At the same time. these sensitive ecosystems are vulnerable because of the extension of agricultural land, the extraction of timber, mining activities, the tapping of water resources and similar anthropogenic intrusions. Ethno-specific knowledge of the tropical rainforest ecosystem was determined in sample communities of the Shuar, the Saraguros and the Mestizo-Colonos – particularly with respect to the natural forest resources and their uses. Ethnoecological and agrogeographical research methods were used to document the indigenous knowledge of traditionally utilized wild and eultivated plants, to analyze current forms of land use (including the traditional cultivation of forest and home gardens), and to evaluate ethno-specific survival strategies and strategies of biodiversity managemen
UnivIS-Import:2015-03-09:Pub.2006.nat.dgeo.IG.LGIPDH.tradit

Useful plants and weeds occurring in Shuar, Saraguro, and Mestizo communities. Checklist Reserva Biológica San Francisco (Prov. Zamora-Chinchipe, S. Ecuador) - Gerique-Zipfel, Andres; Veintimilla, Darío (Ecotropical Monographs, 2008)
UnivIS-Import:2015-04-20:Pub.2008.nat.dgeo.IG.zentr.useful

Waldschutz durch Zahlungen für Ökosystemleistungen? Eindrücke aus dem ecuadorianischen Amazonas - Gerique-Zipfel, Andres (Mitteilungen der Fränkischen Geographischen Gesellschaft, 2020)
Die Honorierung von Ökosystemleistungen (Payments for Ecosystem Services PES) ist ein vielverspre-chendes aber auch oft kritisiertes Instrument im Kampf gegen die Zerstörung der tropischen Wälder und den Klimawandel. In Ecuador, eines der biodiversitätsreichsten Länder der Welt, wird seit 2008 Socio Bosque (SB) angewendet. Es handelt sich um ein PES-Programm für den Schutz der Wälder, in dem die individuellen und kommunalen Waldeigentümer freiwillig teilnehmen können. Diese Arbeit untersucht anhand qualitativer Interviews in den Amazonas-Provinzen von Zamora-Chinchipe und Pastaza die Mo-tivation und die Zufriedenheit der Teilnehmer mit diesem Programm. Die Ergebnisse zeigen, dass SB ein hochgeschätztes Programm ist und dass es zum Schutz der Wälder beiträgt, zumindest in Gebieten, in denen andere gewinnbringende Aktivitäten kaum möglich sind. Darüber hinaus scheint SB eine wichtige Unterstützung gegen Armut zu sein und verstärkt die Institutionen der indigenen Völker. Gleichzeitig erhöht SB die Abhängigkeit der kleinen, isolierten indigenen Gemeinden von ihren Vertretern und der Arbeit der NGOs. Die Kriterien, mit denen das Umweltministerium die Anträge genehmigt, müssten in Anbetracht der mangelnden finanziellen Mittel überarbeitet werden. Eine Novellierung des Programms sollte mit der Ein-wirkung der Waldbesitzer durchgeführt werd

What Is Behind Land Claims? Downsizing of a Conservation Area in Southeastern Ecuador - Gerique-Zipfel, Andres; López Sandoval, María Fernanda; Pohle, Perdita (Sustainability, 2017)
Keywords: Ecuador; conservation areas; downsizing; land claims